2001
DOI: 10.1029/2001ja900080
|View full text |Cite
|
Sign up to set email alerts
|

Source of field‐aligned irregularities in the subauroral F region as observed by the SuperDARN radars

Abstract: Abstract. The HF radars of the Super Dual Auroral Radar Network (SuperDARN)observe the E x B convective drift, of ionospheric plasma when suitable small-scale field-Migned irregularities (FAI) from which to scatter are present. In order to estimate the distribution of FAIs in the subauroral F region, we have investigated the scattering occurrence percentage using data from six Northern Hemisphere radars during 39 months between July 1995 and September 1998. We have ident, ified a morphological tbature known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
49
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(60 citation statements)
references
References 28 publications
9
49
2
Order By: Relevance
“…Milan et al (1997) clearly demonstrated that Hankasalmi daytime echoes are typically cusp/cleft echoes obtained through this mode, and other reports (e.g. Ruohoniemi and Greenwald, 1997;Hosokawa et al, 2001) support this conclusion.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Milan et al (1997) clearly demonstrated that Hankasalmi daytime echoes are typically cusp/cleft echoes obtained through this mode, and other reports (e.g. Ruohoniemi and Greenwald, 1997;Hosokawa et al, 2001) support this conclusion.…”
Section: Discussionsupporting
confidence: 70%
“…3, indeed echoes started to be observed more frequently right after the local sunset for the F-region, so the horizontal plasma gradient associated with the trough might have contributed well to the preferential irregularity formation during these hours. In addition, Hosokawa et al (2001) did find a second morning peak in echo occurrence for the Canadian radars, but not for the Hankasalmi radar. In our event, quite a few echoes were observed during morning hours on 10 and 11 February and perhaps on 9 February (EISCAT measurements are not available here, but Sodankylä ionosonde data support this conclusion) prior to local sunrise.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Huber (1999) explored Saskatoon radar data for 1997 and reported that wintertime F region echoes are mostly detected in two time sectors: near noon and later in the afternoon close to the dusk sector. Hosokawa et al (2001) merged SAS data with data from other Canadian radars for periods of solar minimum and showed that winter and summer time echoes are more frequent on the dayside and nightside, respectively. They also noticed a separate region of enhanced echo detection in the afternoon-dusk sector and related those to the sectors of favorable conditions for the gradient drift instability operation in the ionospheric trough which is highly expected at these latitudes and during these hours.…”
Section: Discussionmentioning
confidence: 99%